If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 10 = -10 Reorder the terms: 10 + x = -10 Solving 10 + x = -10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + x = -10 + -10 Combine like terms: 10 + -10 = 0 0 + x = -10 + -10 x = -10 + -10 Combine like terms: -10 + -10 = -20 x = -20 Simplifying x = -20
| y=4+0 | | -11=x+3 | | 2u^2-7u-5=0 | | y+x=7 | | 45w^2-6w-5=0 | | (5a+3b)(4a-b)= | | 90w^2-30w-25=0 | | 6.5=3x+7 | | -6.5(4y+6)-2.9(3y-5)= | | 395+77x=1319 | | -6x-20=-6 | | (4x+y)(3x-4y)= | | 5x-7=2x-34 | | -6x+20=-6 | | (6x-y)(3x-2y)= | | 290+74x=1474 | | -6(2p+4)-36=4(3p+3) | | -2(0)-6y=6 | | (x+2y)(2x+3y)= | | x^2=-6 | | 7-10n+5n=22-90 | | (-x-4)(4+3x)= | | 3-2=1 | | 4x^2=8x+5 | | 4(c-5)+9=6+c-17 | | 4y=8x-12 | | v^2x^2-9x^2+v^2n^2-9n^2=0 | | 5a-8.7=2.6a-2.22 | | 3(0)-4y=24 | | 2a+1.8=4.3a-14.99 | | 3x-4(0)=24 | | (2x+5)(4x-3)= |